EFFECT OF PREGNANCY EXERCISE ON DURATION OF THE FIRST AND SECOND STAGE OF LABOR IN PRIMIGRAVIDA MOTHERS DURING THE THIRD TRIMESTER OF PREGNANCY - Iin Wahyuni; Noor Pramono; Titi Suherni; Melyana Nurul Widyawati (Belitung Raya Foundation, Indonesia, 2017)
Objective: This study aimed to examine the pregnancy exercise during the third trimester of pregnancy on duration of the first and second stage of labor in primigravida at the Community Health Center of Sukamaju, Bandar Lampung, Indonesia. Methods: This study employed a quasi-experimental design with posttest-only non-equivalent control group. This study was conducted from 8 January 2017 to 12 February 2017 at the Community Health Center of Sukamaju. Forty-eight primigravida mothers were selected using consecutive sampling, with 24 assigned in the experiment and control group. Data were analyzed using Mann Whitney and Chi Square test. Results: The average duration of the first stage of labor in the experiment group was 495 minutes and in the control group was 685 minutes (p= 0.000); while the average duration of the second stage of labor in the experiment group was 42.5 minutes and in the control group was 68.75 minutes (p=0.000). Conclusion: There was a statistically significant difference in the duration of the first and second stage of labor between experiment and control group. It is expected for midwives in the community health centers to implement pregnancy exercise program to help mothers in accelerating the delivery process.